ANALISIS TINGKAT PRODUKTIVITAS DAN PENDAPATAN PENYADAP GETAH PINUS DI RESORT PEMANGKUAN HUTAN KARANGHARJO KESATUAN PEMANGKUAN HUTAN BANYUWANGI SELATAN - Ahlan, Azdi Faraihan; Setiawan, Budhy; Fahrussiam, Fauzan (AGRICA, 2025)
Perum Perhutani, the South Banyuwangi Forest Management Unit (KPH) produces pine sap as a commodity for non-timber forest products. The collection of pine sap in the FMU area involves members of the community around the forest. The level of eavesdropping revenue is greatly influenced by the productivity of tapping. Therefore, this study aims to find out the level of pine sap productivity that affects the income of tapers and the level of welfare of tapers. The determination of the plots was carried out by purposive sampling so that 4 plots were selected: 19A-1, 19C, *26E-1, and *26E-3. The determination of the plot using a sampling intensity of 1% was obtained with 16 plots determined by the plot demonstration method. Data collection was carried out by census method. The results of the study showed that (1) the average productivity of pine sap in RPH Karangharjo was 6.10 grams/tree/day. (2) Eavesdropping income who only works as a eavesdropping has an average income of Rp. 15,624,000 per year, while eavesdropping with additional work has an average total income of Rp. 17,627,142 per year. (3) Based on World Bank standards, 100% of eavesdropping is classified as prosperous, but according to the Banyuwangi Regency MSE, there are only 52.38% who are prosperous and the rest are not. Further research is needed related to factors that can affect the productivity of pine sap on eavesdropping revenue.